Influence of Salt Doping on the Entropy‐Driven Lower Disorder‐to‐Order Transition Behavior of Poly(ethylene oxide)‐b‐Poly(4‐vinylpyridine). Issue 24 (22nd October 2021) - Zhang, Ze‐Kun; Ding, Shi‐Peng; Zhou, Yi‐Ting; Ye, Ze; Wang, Rui‐Yang; Du, Bin‐Yang; Xu, Jun‐Ting
Abstract: Poly(ethylene oxide)‐ b ‐poly(4‐vinylpyridine) (PEO‐ b ‐P4VP) block copolymers (BCPs) exhibiting lower disorder‐to‐order transition (LDOT) phase behavior are doped with different salts (LiCl, CuCl2, and FeCl3 ), in which both blocks can competitively associate with the metal ions. It is found that the entropy‐driven LDOT phase behavior of PEO‐ b ‐P4VP can be bi‐directionally adjusted by enthalpic interactions, depending on the complexation selectivity of metal ions toward two blocks and doping ratio ( r ). At low r s, Li + ions preferentially interact with PEO block, leading to a decreased disorder‐to‐order transition temperature ( T DOT ). Cu 2+ ions selectively complex with the P4VP block, and the T DOT first increases with increasing r, followed by a decrease. By contrast, Fe 3+ ions interact strongly with both blocks, resulting in increase of T DOT . At high r s, the complexation selectivity becomes weaker, leading to reduced immiscibility and increased T DOT, as compared with the hybrids with low r s. The effects of metal cation and r on the LDOT phase behavior are qualitatively explained by the change of the Flory–Huggins parameter. Abstract : The entropy‐driven lower disorder‐to‐order transition (LDOT) of poly(ethylene oxide)‐ b ‐poly(4‐vinylpyridine) (PEO‐ b ‐P4VP) is regulated by salt‐doping, i.e., enthalpic interaction. The transition temperature can be bi‐directionally adjusted due to the competitive complexation of metal ions with the PEO and P4VP blocks. This provides a more direct and convenient avenue to regulate the LDOT phase behavior of block copolymers.